PERSEPSI GURU TERHADAP PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DI SMK NEGERI KELOMPOK BISNIS MANAJEMEN KOTA PADANG - Vajar Makna Putra (Jurnal Bahana Manajemen Pendidikan, 2014)
This study aimed to obtain information about teachers' perceptions of the principal's decision in SMK Padang Management Business Group. The population was sampled 133 teachers and 54 teachers were taken with a random sampling technique. The research instrument was a Likert scale questionnaire form has been on test validity and reliable. Data were analyzed using the average value (the mean). The results of this study are the perceptions of teachers to the principal decision-making at SMK Padang Management Business Group in good enough category. Kata Kunci : persepsi; pengambilan keputusan